Intracellular RNA delivery by lipid nanoparticles: Diffusion, degradation, and release. (November 2019) - Zhdanov, Vladimir P.
Abstract: Various RNAs (siRNAs, miRNAs, or mRNAs) can be delivered into cells by lipid nanoparticles (LNPs) of 50–150 nm in diameter. The subsequent RNA release from LNPs may occur via various scenarios. Herein, two related kinetic models are proposed. The first model takes into account that LNPs are often porous so that RNA molecules diffuse in and detach from nanopores. The analysis is focused on RNA diffusion from a pore. The analytical expression obtained for the RNA escape rate constant is used to identify the difference in the release of siRNAs, miRNAs, and mRNAs. The key message here is that the mRNA diffusion from pores appears to be too slow, and accordingly the mRNA release seems to occur primarily via degradation of LNPs. The second coarse-grained model describes the diffusion-mediated release of RNA from a LNP in the situation when this process is accompanied by the LNP degradation at the lipid-solution interface. The corresponding kinetics are shown in detail at different relative rates of the RNA diffusion and LNP degradation. Potentially, this can help to interpret drug plasma levels after various dosing regimens.